Analysis on Relational-Understanding in Solving Problem for Field Independent Students - Yazidah, Nok Izatul; Argarini, Dian Fitri; Sulistyorini, Yunis (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
This research is triggered by one of mathematics learning objectives in Senior High School which is about understanding mathematics concept. Based on the result of the observation and the conducted interview with mathematics teachers, it is said that on learning Combinatorica, students are always less of ability to solve the problem, sometimes students’ answer only focus on what is being asked. The purpose of this reasearch is to describe students’ relational understanding in solving problems for FI students based on the gender. The subjects of this research are Senior High School students having field independent cognitive style in Malang and have been choosen randomly. The subjects consist of two students, a boy and a girl. The instruments needed in this research are sheet of GEFT test, sheet of Combinatorica questions, and interview sheet. The result of this research states that FI girl student has ability on relational understanding as the same as the FI boy students has. But the process in solving problem made by the boy student is likely similar to the accurate process in solving problems.